PENGEMBANGAN BAHAN AJAR BIOLOGI SEL PADA PROGRAM STUDI PENDIDIKAN BIOLOGI UIN ALAUDDIN MAKASSAR - Muriati, St (Jurnal Florea, 2014)
Learning in UIN Alauddin is still limited knowledge to students, while, one mission to improve the quality of educators Biology in terms of belief, moral and scientific attitudes have not been implemented. This is caused by a lack of learning resources that connects Biology Science and its relation to scientific Quran. Cell Biology as subjects that reveal about the phenomenon of the smallest unit of life, it can be studied with scientific Quran. Therefore, it is necessary to develop teaching materials of Cell Biology with scientific Quran to achieve one mission in Biology Education Courses of UIN Alauddin Makassar to improve quality in terms of the creed of Biology Educators, moral and scientific attitude. Cell Biology purposes of teaching materials even this can help students to better understand the concept of Cell Biology abstract to concrete, because in Cell Biology teaching materials displayed image by using a reference cell that contains the results of research conducted by experts Cell BiologY. Thus, the implementation and achievement of learning objectives can be achieved optimally so that it can support contextual learning of Cell Biology. Keyword : development, instructional materials, cell biology